A STUDY ON THE IMPETUSES AND CONTESTS IN THE ESPOUSAL OF CRYPTOCURRENCY AS A MEDIUM OF EXCHANGE IN INDIA - Ramprakash, K.R. (Digital Repository of Theses - SSBM Geneva, 2022)
The deciding factor in the emergence of cryptocurrency as a global currency depends on the level of acceptance it gains in society. While cryptocurrency is gaining significant acceptance in developed economies like the US, the adoption rate in emerging economies like India has not been studied. Cryptocurrency must be adopted in countries like India to become an actual global currency. Hence, the study aims to determine the factors affecting the adoption of cryptocurrency as a medium of exchange in India. Design /Methodology The study is based on primary data collected from a targeted sample of 750 respondents. A theoretical model based on UTAUT and TTAT was developed. A purposive sampling technique was adopted for the study, and the required data were collected using a well-structured and pre-tested questionnaire. PLS-SEM analysis has been used to assess the theoretical model of the study. Findings The study established that perceived threat, attitude, and social influence are the significant factors affecting the adoption of cryptocurrency in India. Effort expectancy and performance expectancy have a considerable impact on the intention to use via attitude. In contrast, perceived severity and perceived susceptibility significantly affect the intention to use via vi perceived threat. Financial literacy and facilitating conditions don’t seem to impact the intention to use cryptocurrency as a medium of exchange in India. Research Limitations The study is limited to respondents in the major cities of India, and only people who are cryptocurrency investors were purposively selected for the study. Thus, future studies could examine the perception of people who are not cryptocurrency investors. Furthermore, future studies can also investigate other factors that affect the intention to use cryptocurrency, such as social media influence. Originality This might be the first study that combined UTAUT and TTAT models to assess the factors affecting the adoption of cryptocurrency. Further, this study attempted to capture the perception of Indian cryptocurrency investors, and thus, the results will be helpful for policy and decision-makers while adopting regulatory measures.